Determination of oral feeding skills in late preterm, early term, and full-term infants using the neonatal oral feeding monitor (NeoSAFE) - Ayse Ecevit; Balkar Erdogan; Deniz Anuk Ince; Meltem Aksu; Sezin Unal; Özden Turan; Ahmet Saracoglu; Aylin Tarcan (Italian Journal of Pediatrics)
Abstract Background Mature oral feeding is a complex function involving numerous muscles and nerves, typically developing between the postmenstrual age of 34–36 weeks in newborn infants. The objective of this study was to analyze the oral feeding skills of healthy late preterm, early term, and full-term infants using a neonatal oral feeding monitor. Methods We used the oral feeding parameters reported by NeoSAFE which is a certified medical device, to assess the swallowing and swallow-respiration coordination in newborn infants. Oral feeding parameters were recorded over a 2-minutes long bottle-feeding session. The total swallow count, swallow time, maximum rhythmic swallows, resting interval duration, time between rhythmic swallows and inspiration after swallow count were recorded by NeoSAFE. We planned to examine the relationship of oral feeding parameters according to the gestational age. We also investigated whether the coordination of swallowing and respiration changes with respect to gestational age in newborn infants. Results A total of 88 infants were included; 34 late preterm, 34 early term, and 20 full term. The gestational age was found to have significant negative correlation with the average time between rhythmic swallows and positive correlation with the swallow time. Feeding volume was found to have a negative correlation with the resting interval duration and average time between rhythmic swallows. It was also found that the feeding volume has a positive correlation with total swallow count, swallow time, maximum rhythmic swallow and inspirium after swallow count. Conclusion Although the oral feeding skills of infants at 34 weeks gestation are still developing, this study identified differences in oral feeding skills among late preterm, early term, and full-term infants when assessed using a neonatal swallow and respiration detection system. However, conducting larger cohort studies using NeoSAFE would be beneficial for guiding oral feeding approaches in infants. Trial Registration Not applicable.